Palestinian Women's Activism : Nationalism, Secularism, Islamism - Jād, Iṣlāḥ (Book collections on Project MUSE., 2018)
The political and public life of Palestinian women has been influenced by a number of factors, most importantly successive waves of occupation of Palestine by various forms of colonization; the evolution and growth of the Palestinian national resistance movement; development of the national movement (later the Palestinian Authority); and the evolution and growth of the feminist movement. This book analyses the structural and ideological transformations of the contemporary Palestinian women's movements in the aftermath of the signing of the Oslo Agreement in 1993 between Israel and the PLO. Based on in-depth interviews with male and female activists and members of different organisations, I provide an analytical overview of the evolution and current configuration of the contemporary women's movements. A detailed analysis of the discourses and structures of the mass-based organisation (PFWAC), the women's NGO (WCLAC) and the women's division of Hamas (studied for the first time) is presented.